Sistem Penghitung Jumlah Orang Otomatis Pada Pintu Masuk Berbasis Sensor Ultrasonik dan Mikrokontroler Arduino Uno dengan Metode Bayes - Eko Ardiansyah; Hurriyatul Fitriyah; Dahnial Syauqy (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Count the number of visitors in shopping centers can provide a management information to optimize place , and evaluate attractiveness on some areas shopping .Area manager able to analyze monitor the state of the crowd. From what it is all about built with the sweat of , he or she needs a automatic system used to calculate the total number of people through the trap door .In this research , parameter that used of these tests are the detection of an object which prevailed over you and. This instrument will be means of sensors ultrasonic hc-sr-04 processed use classifications bayes & apos; to count the number of people get past the sensors ultrasonic on the door.On the system that they used mikrokontrolet ardino uno used to menggontrol system and output will be displayed in lcd 16x2. A method of bayes ' was selected as one technique for a decision making classifications counters the number of people through the door at the same time , this method is one of the classification methods that is simple enough and understandable .So that the kind of accuracy that obtained this system by using the method non-competitive purchase will be 80 %. The result of testing time performed as many as 10 times, the obtained from pengamilan rata-rata system decision by 679,2 ms. Bayes In this case using the size of the door wide 200 cm in size and 190 cm high.